I believe it's increasing on all fronts, because if you start from the right, you see that the y values always increase, hence they are increasing. They do it for when x<0 and when x>0. So, it should be increasing on all real numbers
Answer:
x = - 1
Step-by-step explanation:
3(x + 1) = - 2(x - 1) - 4 ← distribute parenthesis on both sides
3x + 3 = - 2x + 2 - 4
3x + 3 = - 2x - 2 ( add 2x to both sides )
5x + 3 = - 2 ( subtract 3 from both sides )
5x = - 5 ( divide both sides by 5 )
x = - 1
Answer:
The answer to your question my friend is Y = -1, 3 x
Step-by-step explanation:
I am making my best guest so that I can answer your question since no one will
Thx and have a blessed day
Answer:
The value of h for given value of p is 9950
Step-by-step explanation:
Given as :
The equation - p + 60 = - h + 10,000 Where h is constant
Now, for p = 10 ,
h = 10,000 + p - 60
Or, h = 10,000 + 10 - 60
Or, h = 10,000 - 50
∴ h = 9950
Hence The value of h for given value of p is 9950 Answer